Graduate migration in Italy - Lifestyle or necessity? - Elisabetta Marinelli (European Regional Science Association (ERSA), 2011)
This paper studies the locational choice of Italian mobile graduates, tackling simultaneously three aspects. First it analyses the structural drivers of migration (i.e. the key regional characteristics that attract high-skilled migrants) and the social structures that underpin it (i.e the role of migration networks). Secondly, it compares the preferences of migrants across Italy, to those who move from the least developed South to the Centre-North and those who move within the richer Centre-North. Thirdly, as graduate migration is a key mechanism to transfer knowledge from the university to the labour market, particular attention is given to migrants who are applying, in their jobs, exactly the skills gained through their degree. Results indicate that social networks are a much stronger determinant of the destination of graduates than regional characteristics, that to apply one's knowledge it is necessary to move to highly innovative areas, and that graduates from different areas have different preferences and behaviour. In particular, whilst migration is a lifestyle choice for those who move within the Centre-North, it is driven by economic necessity for those who leave the South.
Keywords: 330